2014
DOI: 10.1002/j.0022-0337.2014.78.4.tb05702.x
|View full text |Cite
|
Sign up to set email alerts
|

What Dental Educators Need to Understand About Emerging Technologies to Incorporate Them Effectively into the Educational Process

Abstract: Many dental schools are currently struggling with the adoption of emerging technologies and the incorporation of these technologies into the educational process. Dental students exhibit an increasing degree of digital comfort when using social networking, mobile devices, search engines, or e-textbooks. Although the majority of students might consider themselves to be very skilled at using information technology, many faculty members would claim the opposite when evaluating their own knowledge and skills in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Many students fail to see the educational value tools they use routinely for other purposes. Dental students associate social networking services with private discussions and not with dental school interactions 20 . Students should been given explicit guidance on how to make best use of social media in their education and set specific objectives 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Many students fail to see the educational value tools they use routinely for other purposes. Dental students associate social networking services with private discussions and not with dental school interactions 20 . Students should been given explicit guidance on how to make best use of social media in their education and set specific objectives 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The high number of undecided faculty members demonstrates a level of hesitancy we have observed at many dental schools. Digital reference libraries offer a number of advantages over printed books, including searchability, enhanced display of images, more frequent updates, ease of carrying large number of texts around, links to updated websites, and taking and sharing digital notes across multiple users; but those advantages are sometimes lost on faculty members who feel challenged by the array of digital opportunities 12 …”
mentioning
confidence: 99%
“…Many institutions of higher education have started adopting the use of electronic textbooks in their programming, and similar to attitudes identified in students, faculty have met the shift with mixed perceptions. In a study conducted by Stein et al, results revealed that faculty both supported and hesitated in their adoption of electronic textbooks.…”
Section: Introductionmentioning
confidence: 99%